SEMANTIC CHANGE AND MEANING SHIFT ANALYSIS ON NARRATIVE TEXTS’ DIALOGUES AMONG THE CHARACTERS IN THE SECOND YEAR ENGLISH TEXTBOOKS OF SENIOR HIGH SCHOOL - Dede - Narawaty (Universitas Nasional, 2017)
ABSTRACT The purposes of this study are to (1) describe the types of semantic change existing in characters’ dialogues of the narrative text in high school English textbooks class X; (2) distinguish the conceptual meaning and new meaning in characters’ dialogues of the narrative text; and (3) show the cause of meaning shift in characters’ dialogues of the narrative text. This research approach uses a qualitative approach with descriptive methods, because it deals with the qualitative data, the corpus of words. These research findings both in the textbooks The Spotlight containing seven narrative texts and Real Time containing six narrative texts. They indicate a change and a shift in meaning as a result of the contexts of the use of language.) Key Words: semantic change, meaning shift, narrative texts’ dialogues, characters ABSTRAK Penelitian ini bertujuan (1) mendeskripsikan jenis perubahan semantik dialog antartokoh dalam teks naratif pada buku bahasa Inggris SMA kelas X; (2) membedakan makna konseptual dan makna baru dalam dialog antartokoh dalam teks naratif; dan (3) menunjukkan penyebab pergerseran makna dalam dialog antartokoh dalam teks naratif. Pendekatan penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif karena berkenaan dengan data kualitatif, yakni korpus kata. Hasil temuan penelitian ini baik pada buku teks The Spotlight yang memuat 7 teks naratif maupun buku teks Real Time yang memuat 6 teks naratif, keduanya menunjukkan adanya perubahan dan pergeseran makna sebagai akibat dari konteks penggunaan bahasa. Kata Kunci: perubahan makna, pergeseran makna, teks naratif ‘dialog’, karakter